PENERAPAN METODE BERCERITA BERBANTUAN MEDIA AUDIO VISUAL UNTUK MENINGKATAN KETERAMPILAN BERBICARA SISWA KELASⅡSEKOLAH DASAR UPT SDN 004 SALO - Mardianti, Alaina; Hana Pebriana, Putri; Ananda, Rizki; Aprinawati, Iis; Nasrul (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
The background of this research is the low speaking skills of second-grade students due to the dominant use of lecture-based teaching methods, which highlights the need for implementing a more appropriate instructional method. This study aims to improve the speaking skills of early grade students through the application of storytelling methods assisted by audiovisual media. The study was conducted in a public elementary school with 17 students as subjects, using a Classroom Action Research (CAR) approach consisting of two cycles. Each cycle includes planning, implementation, observation, and reflection. The research instrument was an observation sheet of teacher and student activities and an assessment of speaking skills. The results of the study showed an increase in students' speaking skills at each meeting. In Cycle I Meeting I, the average student speaking skills reached 64.71 (Poor category) with 9 students completing (52.94%), increasing in Cycle I Meeting II to 74.12 (Sufficient category) with 12 students completing (70.59%). Furthermore, in Cycle II Meeting I, the average reached 81.96 (Good category) with 14 students completing (82.35%), and Cycle II Meeting II the average was 88.63 (Good category) with 15 students completing (88.24%). This increase indicates that the storytelling method assisted by audiovisual media is effective in improving students' speaking skills. Thus, it can be concluded that the application of storytelling methods assisted by audiovisual media can improve the speaking skills of second-grade students at SDN 004 Salo.